Uruguay's Energy Transition and Intergenerational Justice in the Framework of Ecological Jurisprudence - Edor, Edor John; Ncha, Gabriel Bubu; Etta, Robert Bikom; Odey, Elizabeth Akpanke; Eneji, Gabriel Ajor; Ellah, Timothy Ogbang; Effiong, Eke Nta (NAJAHA, 2025)
The global transition from fossil fuels to renewable energy is one of the most pressing environmental and social challenges of the 21st century. From an ecological jurisprudential perspective, this process is closely linked to the principle of intergenerational justice, which requires states to guarantee the environmental rights of future generations. This study aims at two things: first, to provide a critical legal analysis of Uruguay's fossil fuel transition within the framework of intergenerational justice; and second, to develop a replicable analytical model for assessing energy transitions in developing and middle-income countries, with implications for global debates on sustainability, ecological ethics, and intergenerational equity. The research method uses an interpretive qualitative paradigm with a case study design in Uruguay, through semi-structured interviews, non-participant observation, and analysis of legal-policy documents, accompanied by data triangulation and thematic analysis. The results reveal two main findings. First, there is a tension between substantive success, nearly 98% of Uruguay's electricity is based on renewable energy and normative weakness in the absence of explicit protection of the rights of future generations in the legal framework. This indicates a strong de facto sustainability but a fragile de jure one heavily dependent on political commitment. Second, this research produces the IEJET (Intergenerational Ecological Justice Energy Transition) Model, which assesses the energy transition through four stages: national context, legal framework, substantive-normative dimensions, and the principle of intergenerational justice. The research's limitation lies in its focus on the electricity sector, thus under-exploring aspects of transportation, industry, and global political economy. Consequently, the technical success of the energy transition is insufficient without strengthening laws, institutions, and intergenerational participation. An original contribution of this research is developing the IEJET conceptual framework as an evaluation tool that strengthens the discourse of global ecological justice.